Effectiveness of transabdominal ultrasonography in assessing benign versus malignant nature of prostatomegaly - Shareef, Saad; Joshi, Anil (International Journal of Research in Medical Sciences, 2019)
Background: Benign prostatic hyperplasia is closely related with ageing. The present study was conducted to assess the ability of transabdominal ultrasonography in diagnosing benign and/or malignant hypertrophy of the prostate. Methods: An observational study was done in the Department of Radiology, Bharati Vidyapeeth Medical College and Hospital (Deemed to be University), Sangli, Maharashtra, India of patients who had prostatomegaly on transabdominal ultrasound examination and underwent histopathological confirmation of the lesions from 1 October 2018 till 31 December 2018. The prostate gland was assessed for volume, echotexture, morphology, focal lesions and median lobe. Results: Out of 155 patient’s benign prostatic disease was diagnosed in 116 patients, while malignancy was detected in the rest of the 39 cases. Prostate specific antigen levels were significantly higher among malignant cases (18.39±7.44 ng/ml) as compared to that of benign cases (7.51±3.22 ng/ml), p value <0.01. Benign lesions were predominantly inner glandular, while malignant cases were mainly peripheral. Moderate vascularity was found in 76.9% of the malignant cases. Focal vascular asymmetry was found in 74.4% of the malignant cases and only 12% of the benign cases. Sensitivity of transabdominal ultrasonography in diagnosing malignant prostatic lesions was 94.8%, specificity was 75% with an overall accuracy of using transabdominal ultrasonography in the diagnosis of malignant prostatic lesions in this study population was 80%. Conclusions: Transabdominal ultrasound evaluation of prostate is a simple, economical, non-invasive technique of choice due to its high accuracy in detecting size, nature of pathology as benign or malignant with fair accuracy.